Complex Network Phenomena in Telecommunication Systems - Laura A. Schintler; Sean P. Gorman; Aura Reggiani; Roberto Patuelli; Andy Gillespie; Peter Nijkamp; Jonathan Rutherford (Tinbergen Institute, 2004)
Many networks such as the Internet have been found to possess scale-free and small-world network properties reflected by so-called power law distributions. Scale-free properties evolve in large complex networks through self-organizing processes and more specifically, preferential attachment. New nodes in a network tend to attach themselves to other vertices that are already well-connected. Because traffic is routed mainly through a few highly connected and concentrated vertices, the diameter of the network is small in comparison to other network structures, and movement through the network is therefore efficient. At the same time, this efficiency feature puts scale-free networks at risk for becoming disconnected or significantly disrupted when super-connected nodes are removed either unintentionally or through a targeted attack or external force. The present paper will examine and compare properties of telecommunications networks for both the United States and Europe. Both types of networks will be examined in terms of their network topology and specifically whether or not they are scale-free networks to be further explored by identifying and plotting power law distributions. Next, economic, political and cultural factors may be used to explain differences in network structures between the United States and Europe. In addition, the paper will identify data and modeling tools that are needed to facilitate further cross-Atlantic comparative studies of communications networks.
Keywords: L96; D85; C16; 330; complex networks; telecommunications; power law distributions; exponential distributions; Europe and US; Telekommunikationsnetz; Telekommunikationsnetz; Internet; Deregulierung; Netzregulierung; Vergleich; Europa; USA